ANALISIS KADAR FLAVONOID TOTAL INFUSED WATER CHIA (Salvia hispanica L.) SEED DENGAN VARIASI LAMA PENYIMPANAN SECARA SPEKTROFOTOMETRI UV-Vis - Dewi Nur Istikhomah; Dhurhania, Crescentiana Emy (Jurnal Insan Farmasi Indonesia, 2025)
Chia Seed contains antioxidants that found in flavonoid compounds. Antioxidants play an important role in warding off free radicals that damage cells and body tissues. This study aims to determine the total flavonoid content of infused water chia seeds (Salvia hispanica L.) with variations in storage time using the UV-Vis spectrophotometric method. Qualitative analysis with HCl and Mg metal, 10% NaOH and H2SO4 reagents with positive results containing flavonoids. Quantitative analysis uses UV-Vis spectrophotometry with a stable operating time of 28 minutes and a wavelength of 440 nm. The results of determining total flavonoid levels obtained from infused water chia seeds at a variation of 12 hours of storage time was 53.237 ± 0.246726 mgQE/ 100 ml, 10 hours of storage time was 51.862 mgQE/ 100 ml, and 8 hours was 30.381 mgQE/ 100 ml. ml. With prolonged storage, a diffusion process occurs which causes flavonoid levels to increase. The One Way Anova test obtained a significant value of 0.000 < 0.05 and the Post Hoc Test obtained a significant value of 0.000 < 0.05 so it can be concluded that there are real differences between the three variables.